Christianity and mankind: their beginnings and prospects - Bunsen, Christian Karl Josias (Longman, Brown, Green, and Longmans, 1854)
v. 1-2. Hippolytus and his age; or, The beginnings and prospects of Christianity.--v. 3-4. Outlines of the philosophy of universal history, applied to language and religion.--v. 5-7. Analecta ante-nicaena.